2009
DOI: 10.1099/jmm.0.002105-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic assays for detecting the prevalence of metallo-β-lactamases in clinical isolates of Acinetobacter baumannii from a South Indian tertiary care hospital

Abstract: Nosocomial infections caused by Acinetobacter baumannii often prove difficult to treat owing to their multiple drug resistance. Carbapenems play a pivotal role in the management of severe Acinetobacter infections. However, reports of carbapenem resistance have been increasing alarmingly due to production of a variety of carbapenemases including metallo-b-lactamases (MBLs). This study investigated by both phenotypic and genotypic assays the prevalence of MBLs in a total of 55 A. baumannii strains isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 26 publications
9
51
1
Order By: Relevance
“…Overall MBL production was found quite significant 88% (88/100) among our isolates close to a study by Uma et al, (2009) reporting 70.9 % MBL production. Another Indian study by Shanthi et al, (2009) According to Yong et al, (2002), the imipenem (IMP) 10 μg-EDTA 750 μg combined disc test has 95.7% sensitivity and 91.0% specificity for detection of metallo-β-lactamases in MBL-producing Ps.…”
Section: Fig3 Edta Disc Synergy Test (Eds) Positive Strain Shows a supporting
confidence: 63%
“…Overall MBL production was found quite significant 88% (88/100) among our isolates close to a study by Uma et al, (2009) reporting 70.9 % MBL production. Another Indian study by Shanthi et al, (2009) According to Yong et al, (2002), the imipenem (IMP) 10 μg-EDTA 750 μg combined disc test has 95.7% sensitivity and 91.0% specificity for detection of metallo-β-lactamases in MBL-producing Ps.…”
Section: Fig3 Edta Disc Synergy Test (Eds) Positive Strain Shows a supporting
confidence: 63%
“…In India, MBL production among A. baumannii isolates has been reported at 42%. The most prevalent MBL gene was bla IMP-1 [15]. There is limited data on the prevalence and distribution of metallo-beta-lactamases among Indian isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Hence MHT was positive in 169 isolates (94.4%). The remaining 10 were MHT negative, thereby suggestive of other mechanisms such as loss of porins or upregulation of efflux pumps [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the level of carbapenem resistance was very high in the Baumanii group. Karthika et al (2009) in their study showed the presence of bla IMP1 carbapenemase genes in South Indian population. Though bla VIM-2 is the most common carbapenemases seen in other parts of world (Yum et al, 2002;Poirel et al, 2000;Walsh et al, 2005), it was surprisingly absent in their study, though bla IMP1 gene was seen in 42% of isolates (Karthika et al, 2009).…”
Section: Discussionmentioning
confidence: 99%